Decision making process for prioritizing replacement of medical equipment considering Non-technical Factors - Alqahtani, Tariq Mohamed Y. (British Journal of Healthcare and Medical Research, 2019)
The decision to replace a large number of medical equipments is, necessarily, a multicriteria one. The author work set out to look into the current system being used at the level of the Ministry of Health in the Kingdom of Saudi Arabia to prioritize the replacement of medical equipment. That system, as it operates, is inefficient and does not utilize available resources competently. It relied mostly on technical data and specifications of medical equipment on the replacement list. The author believes that, relevant non-technical data should be used to enhance the quality of replacement prioritization decision. Current decision support systems do not take this into account, this represent a shortfall in existing knowledge. A review of relevant literature of existing Multi-Criteria Decision Making (MCDM) systems, both in the healthcare and other industries, was undertaken. This included AHP, PROMETHEE, VIKOR and Factorial Surveys (vignette). The author chose a new hybrid approach; it included the combination of AHP and vignette. This allowed weighting of non-technical data (identified as attributes throughout the thesis work) and incorporation of responses as obtained from respondents to the vignettes. The hybrid system was tested on the ground by applying it to theoretical medical equipment tender. The author found that, the use non-technical factors have merits in deciding on medical equipment priority replacement list. It is not certain if the newly developed hybrid system would be robust enough to solve the shortcomings of the existing system.